Net-zero greenhouse gas mitigation potential across multi-tier supply chains - Xilin Yang; Timothy M. Smith; Andrea M. Prado; Yi Yang (Communications Earth & Environment)
Abstract Attainment of corporate net-zero goals will depend on sufficient mitigation of scope 3 emissions, but implementation is challenged by measurement and management complexities. Here, we investigate the multi-tier greenhouse gas emissions structures of supply chains to assess mitigation potential using environmentally extended input-output models. We find that 56–70% of scope 3 emissions included in current science-based coverage guidance occur within the operational emissions of the first two tiers of supply. To meet net-zero objectives, companies will typically need to reach deep into tiers 4 or 5 of supply, where traceability has proven impractical. Although the two-tier system is insufficient for net-zero, it could be a near-term strategy with potential benefits of reducing disclosure costs and improving data quality, ultimately increasing scope 3 adoption. Our study highlights opportunities for phased scope 3 coverage provisions in emerging policy, and the allowance of high-quality tradable market mechanisms to aggregate deep mitigation efforts.